Asialoglycoprotein receptor 1: a multifaceted receptor in the liver and cardiovascular system - Xiao, Xuan; Nie, You; Leng, Yiping (Frontiers in Medicine, 2025)
Sialic acid is a common terminal monosaccharide residue on glycan chains, and desialylation of glycoproteins is considered an important biological signal. In the liver and other cell types, asialoglycoprotein receptor 1 (ASGR1) specifically recognizes and binds to exposed galactose or N-acetylgalactosamine (Gal/GalNAc) residues on desialylated glycoproteins, and activates downstream signaling pathways through receptor-mediated endocytosis (RME), thereby playing important roles in various physiological and pathological processes such as immune regulation, viral infection, hepatocellular carcinoma progression, and lipid metabolism. In addition, ASGR1 is regarded as a key target for liver-specific drug delivery. This review systematically describes the molecular structure and physiological functions of ASGR1, its roles in pathological processes, and its potential functions in extrahepatic tissues. It provides essential background information for a comprehensive understanding of ASGR1 and offers novel insights into future research directions.